AN ANALYSIS REVIEW OF INSTAGRAM AS THE MAIN PLATFORM FOR UP-TO-DATE COVID-19 INFORMATION USED BY THE MINISTRY OF HEALTH IN BRUNEI DARUSSALAM - Nurefnazahani Durani; Shereeza Mohamed Saniff (AR-RĀ’IQ, 2024)
With the development of diverse social media platforms such as Instagram, Twitter and YouTube where dissemination of information is limitless. Therefore, social media has become a major source of platform for the public to disseminate and acquire latest information on Covid-19 that happen within their own country or worldwide. Today, the world is still struggling to combat Covid-19 pandemic. Advancement in social media has brought a lot of benefits and drawbacks to a country especially in providing information about Covid-19 in order to prevent and control this pandemic from affecting daily life activities. This study aimed to analyse Instagram posts uploaded by Ministry of Health (MOH) in Brunei Darussalam on their official Instagram account as their main platform to provide information on Covid-19 pandemic to the public. This qualitative study was carried out using the thematic analysis method. Data was retrieved and analysed from the content uploaded from 7th January 2020 until 30th June 2020 on MOH’s Instagram where posts related to Covid-19 in Brunei Darussalam. As result, a total of 487 posts related to Covid-19 pandemic in Brunei Darussalam by MOH for over 6 months were reviewed. Out of 487 posts, 479 had photo-type contents and 28 had video-type contents. The results also discovered that creative info-graphic posts uploaded on Instagram helps to enhance the public knowledge on Covid-19 precautions and this pertinent knowledge contributes to early mitigation of Covid-19 outbreak in Brunei Darussalam.